Prediction of the amino acid digestibility of legume seeds in growing pigs: a meta-analysis approach. (16th October 2017) - Messad, F.; Létourneau-Montminy, M. P.; Charbonneau, E.; Sauvant, D.; Guay, F.
Abstract : On pig farms, a high proportion of the cost of production comes from feed costs. However, the use of alternative ingredients such as legume seeds may help to reduce this cost. In fact, legume seeds are an important source of essential amino acids (EAA) and can therefore be an alternative to oilseed meals. However, the accurate use of these legume seeds requires a precise knowledge of the standardized ileal digestibility (SID) of EAA, which may vary depending on its botanical variety. A meta-analysis was performed on a database compiling data from 41 studies published between 1981 and 2013 and 178 dietary treatments. Models of prediction of the SID of EAA as well as the dietary concentration of digestible standardized EAA (dEAA) were obtained, based on the chemical composition of ingredients reported in the publications. The effect of the type of legume seeds (faba bean, lupin, pea and soya bean), surgical procedures (T-cannula, re-entrant cannulas, post valve T-cannulas and ileo-rectal anastomosis), and BW of pigs (BW⩽25 kg BW>25 kg) were also tested in each model. Results showed that dietary CP and crude fibre (CF) were, respectively, the best predictors of each EAA SID for faba bean, lupin and pea ( R 2 =0.42 to 0.89) and soya bean ( R 2 =0.32 to 0.77). For the dEAA content, the best prediction models included dietary CP and ADF for faba bean, lupin and pea and soya bean, respectively, with R 2 ranging from 0.66 to 0.98. Models developed in this study allow predicting the digestibility of EAA in these alternatives feedstuffs.